Propuesta de un plan estratégico para la empresa Check-Motors de la ciudad de Loja - Cuenca Jaramillo, Ángel Rafael (2015)
Through this research work was the general goal of "PROPOSAL FOR A STRATEGIC PLAN FOR THE COMPANY CHECK-MOTORS OF THE CITY OF LOJA" which allows having an address of company goals accessing achieve stability and permanence in the market and increase the profitability of the company. To meet this goal was necessary to use the historical, deductive, inductive, analytical, descriptive methods, and techniques of the interview the manager and surveys applied to internal customers with a total of 12 and 300 served as external customers sources of information gathering. Further comprising the external analysis of the company of which comes the EFE matrix whose weighted score was 2.58 which is above the average of 2.50; plus the internal analysis of the company that gives rise to the matrix (EFI), the result is 2.58 which is above the average of 2.50. A SWOT analysis of the company is then performed, in which the strengths and weaknesses are exposed; Threats and Opportunities and subsequently high-impact matrix is performed. This determines the strategic objectives, which were, Make a Plan traininga cost of $ 1,365; Perform an advertising plan for CHECK Workshop - MOTORS in order to attract more customers and achieve greater market positioning, with cost of $ 1,410; Making a promotional plan to increase and retain customers with cost of $ 565; Implement manual functions for the CHECK-MOTORS workshop at a cost of $ 1,000; Acquire an accounting program for enterprise CHECK-MOTORS that will cost $ 3,800. The overall budget of the strategic plan was $ 8,140.00. Among the most important findings consist, the company CHECK-MOTORS has opportunities to confront environmental threats, and requires establishing strategies to eliminate them. Among the most important recommendations are, implemented in the company CHECK-MOTORS strategic planning as a mechanism for guidance and business management in each of the areas of the workshop which will help the timely decision making